The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.ijhcs.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Modeling visual sampling on in-car displays: The challenge of predicting safety-critical lapses of control

Abstract: a b s t r a c tIn this article, we study how drivers interact with in-car interfaces, particularly by focusing on understanding driver in-car glance behavior when multitasking while driving. The work focuses on using an incar touch screen to find a target item from a large number of unordered visual items spread across multiple screens. We first describe a cognitive model that aims to represent a driver's visual sampling strategy when interacting with an in-car display. The proposed strategy assumes that drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 32 publications
(49 reference statements)
2
25
0
Order By: Relevance
“…tools (Kujala and Salvucci, 2015), driver education , reactive in-car driver assistance (e.g., lane-keeping assistants) and feedback systems (Donmez et al, 2007), as well as legislative and governmental regulations (NHTSA, 2013b) may help in reducing the negative effects of driver distraction by in-car activities, there is additional demand for fast and cost-effective counter-measures that can be easily deployed by a driver. According to our study, mobile applications aimed to supervise the use of the smart phone while driving and aiding the driver to place more attention on road seems to be a one viable and acceptable option.…”
Section: Discussionmentioning
confidence: 99%
“…tools (Kujala and Salvucci, 2015), driver education , reactive in-car driver assistance (e.g., lane-keeping assistants) and feedback systems (Donmez et al, 2007), as well as legislative and governmental regulations (NHTSA, 2013b) may help in reducing the negative effects of driver distraction by in-car activities, there is additional demand for fast and cost-effective counter-measures that can be easily deployed by a driver. According to our study, mobile applications aimed to supervise the use of the smart phone while driving and aiding the driver to place more attention on road seems to be a one viable and acceptable option.…”
Section: Discussionmentioning
confidence: 99%
“…The EMMA model has been successfully used for simulating gaze patterns in various tasks, such as reading [55], menu search [55], and driving [56,37]. Its main benefit is that it can encode targets without necessarily having to make a saccade.…”
Section: Visionmentioning
confidence: 99%
“…The five motor vehicle studies (Irune & Burnett, 2007;Kim et al, 2014;Kujala & Salvucci, 2015) evaluated target size, target spacing, menu size, and menu arrangement in touchscreen IVIS interfaces on driving performance and secondary task performance; these studies are evaluated in full under RQ2.…”
Section: Interfacementioning
confidence: 99%
“…(2013) compared capacitive and resistive IVIS touch displays, as discussed above under RQ1. Five studies (Irune & Burnett, 2007;Kim et al, 2014;Kujala & Salvucci, 2015) evaluated touch interfaces in IVIS design, including target size, target spacing, menu size, and menu arrangement. Irune and Burnett (2007) reported two studies that evaluated control cluster size and arrangement, control size, and control spacing; they found that higher total control count increased task time, visual demand, and perceived difficulty, identifying clusters of 16 controls or more as resulting in total glance times above 4 seconds; tests of cluster arrangements indicated that increased vertical cluster size in particular yields longer task time and longer total glance time, while increased horizontal cluster size has only a lesser effect.…”
Section: Road Vehiclementioning
confidence: 99%